PERENCANAAN STRATEGI PEMASARAN DENGAN ANALISIS SWOT DALAM UPAYA MENINGKATKAN PENJUALAN SEPATU ADIDAS DI PT. PANARUB INDUSTRY - Suryatman, Tina Hernawati; Kosim, Muhamad Engkos; Samudra, Galuh Eko (Journal Industrial Manufacturing, 2021)
PT. Panarub Industry is a company that produces shoes with the world famous brand, ADIDAS. This study aims to identify internal and eksternal environmental factors that affect the company's business and formulate a type of strategy that is appropriate and can be applied by PT. Panarub Industry in facing business competition. Therefore, companies must determine new strategies to be able to compete in the market. Data collection techniques used were observation, and documentation. To determine new strategies there are several analytical methods that can be used including the IFAS Matrix, EFAS Matrix, SWOT Matrix, and data from the three matrices are analyzed with Cartesian Diagram SWOT Analysis to determine the best and most suitable strategy to be implemented at PT Panarub Industry. Based on the results of the analysis using the IFAS matrix, EFAS, SWOT matrix and Cartesian Diagram SWOT Analysis, the strategy obtained is the strategy that is in quadrant I which means that the strategy used is the Strengths – Opportunities strategy which is also referred to as an aggressive strategy where the position it is a very favorable situation. PT. Panarub Industry has strengths and opportunities so that they can take advantage of existing opportunities. The implementation is maintaining the quality of shoes products, utilizing online marketing to market products by placing advertisements in online shopping applications, social media, and creating corporate websites, and increasing products that are more innovative and varied in order to compete with other shoes companies.Keywords: Strategy, IFAS Matrix, EFAS Matrix, SWOT Matrix, Cartesian Diagram SWOT Analysis